2009
DOI: 10.1007/s12010-009-8678-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antineoplasic Effect of Extracts Obtained from Pleurotus sajor-caju Fruiting Bodies

Abstract: Fungi of the Pleurotus genus present a great industrial interest due to their possibility of producing pharmacological compounds, pigments, aromas, organic acids, polysaccharides, enzymes, vitamins, amino acids, etc. Among the therapeutic products, we can highlight those with antineoplasic activity, attributed to the fungi cell wall components. Based on this, the objective of this work was to study the antineoplasic capacity of the polysaccharidic fractions obtained from Pleurotus sajor-caju fruiting bodies. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…This fact was confirmed by adding YW3548, an inhibitor of glycosylphosphatidylinositol anchor formation, which Uronic acid Gutiérrez et al (1996) 1664 and 1527 Proteins Dalonso et al (2010) 1656, 1654, 1650, and 1642 Amide I (proteins)…”
Section: Biosynthesis Of Glucansmentioning
confidence: 83%
See 2 more Smart Citations
“…This fact was confirmed by adding YW3548, an inhibitor of glycosylphosphatidylinositol anchor formation, which Uronic acid Gutiérrez et al (1996) 1664 and 1527 Proteins Dalonso et al (2010) 1656, 1654, 1650, and 1642 Amide I (proteins)…”
Section: Biosynthesis Of Glucansmentioning
confidence: 83%
“…Masuda et al (2012) demonstrated that purified glucans, such as MD-fraction, a β-(1→3),(1→6)-glucan from Grifola frondosa, and curdlan, β-(1→3) from Alcaligenes faecalis, promote direct production of granulocyte macrophage colony-stimulating factor (GM-CSF), resulting in Dectin-1/Syk activation in resident macrophages. Dalonso et al (2010) studied antitumor activity of extracts from Pleurotus sajor-caju fruiting bodies. Mice were inoculated with the Ehrlich ascitic tumor and the treatment was started after 24 h with polysaccharide fractions, during 6 days, administered intraperitoneally (10 mg/kg).…”
Section: Sparassis Crispamentioning
confidence: 99%
See 1 more Smart Citation
“…1. The biomass was washed with distilled water, frozen, and fractionated according to the methodology proposed by Zhang et al (1994), modified by Dalonso et al (2010). Briefly, 2 volumes of ethanol were added to the frozen mycelial biomass and the suspension was maintained at 80ºC for 3 h. The mixture was centrifuged (3.400 g) and the supernatant containing low molecular weight molecules was discarded.…”
Section: Determination Of Glucose Concentration Wasmentioning
confidence: 99%
“…Moreover, some mushroom compounds, such as polysaccharides, have shown therapeutic effects. Among the effects, the most reported are the antitumoral, antinociceptive, anti-inflammatory, and immunoenhancing activities [3][4][5].…”
Section: Introductionmentioning
confidence: 99%